Effects of seed coat colour on the seed quality and initial seedling growth of red clover cultivars (Trifolium pratense) - Velijević Nataša; Štrbanović Ratibor; Poštić Dobrivoj; Stanisavljević Rade; Đukanović Lana (Journal on Processing and Energy in Agriculture, 2017)
The objective of this study was to investigate the influence of seed coat colour on the seed quality of four red clover cultivars (germination, dormancy (hard seeds), dead seeds and initial seedling growth (vigour)) produced in Serbia over a period of two years. The seeds analyzed were first separated visually into bright, dark and mixed seed groups, followed by subsequent digital colour measurements. The results obtained showed that the seed coat colour of red clover could be considered a good indicator of seed quality and seedling growth ability. The results furthermore showed that bright-coloured seeds of red clover cultivars indicated increased vigour and seed quality compared to other colours. The impact of the production area and year on the seed quality parameters was inconclusive. A high variability in hard (CV = 22.22 %) and dead seeds (CV = 40.18 %) was recorded between different seed lots of red clover. A lower variability was found in the germination parameter of bright- and mixed-coloured seeds (CV = 4.53 % and CV = 8.53 %). The seed coat colour could be an important factor in determining the quality of red clover seeds, potentially increasing germination simply by removing dark-coloured seeds.